New Gymnamoebae Species (Gymnamoebia) in the Fauna of Ukraine - Patsyuk, M.K. (Вестник зоологии, 2012)
Information is given on new in the fauna of Ukraine gymnamoebae species: Saccamoeba stagnicola Page, 1974; Mayorella sp.; Korotnevella sp.; Paradermamoeba levis Smirnov et Goodkov, 1994; Paradermamoeba valamo Smirnov et Goodkov, 1993 and Stenamoeba stenopodia Smirnov, Nassonova, Chao et Cavalier-Smith, 2007.